Early Frontalis Flap Surgery as First Option to Correct Congenital Ptosis with Poor Levator Function. (June 2014) - Medel, Ramon; Vasquez, LuzMaria; Wolley Dod, Charlotte
Abstract In congenital blepharoptosis the upper eyelid cannot be lifted normally because of congenital impairment in the levator function. The descended eyelid margin partially or completely obstructs of the visual axis with the consequent risk of amblyopia. Frontalis suspension is the surgery of choice for ptosis with poor levator function creating a linkage between the frontalis muscle and the tarsus; the frontalis muscle is used to elevate the eyelid. Direct transplantation of frontalis muscle to the upper eyelid has been widely described. We report our experience using frontalis flap in congenital ptosis with poor levator function in children. Methods: Retrospective study of 30 eyes with severe congenital ptosis and poor levator function treated by means of direct frontalis flap. Mean age 2 years. Eyelid measurements were taken at baseline, 1, 3, 12 months postoperatively and last visit. Mean ptosis degree was 5 mm (3--8 mm) and levator function 2 mm (1--5 mm). The presence of complications, flap function and palpebral contour were evaluated. Mean follow up time was 27 months. At last visit, ptosis degree ranged from 0 to 3 mm. Discussion: Direct advancement of the frontalis muscle to treat severe eyelid ptosis is effective and stable in the long term avoiding the use of a linking structure, therefore the risk of foreign-body reaction, absorption, granuloma and late exposure, as well as the need for a second visible incision in the forehead. Patients learn how to control the lid height by means of the frontalis muscle achieving more symmetry.